Use of a wearable device to improve sleep quality - Susan L. Moore; Susan L. Moore; Evan P. Carey; Kristyna Finikiotis; Kelsey L. Ford; Richard D. Zane; Richard D. Zane; Katherine K. Green (Frontiers in Digital Health)
ObjectivesThe present study aimed to analyze the effects of the use of a digital wellness device on improving sleep through reducing environmental noise.MethodsFifty-five self-reported light or moderate sleepers with difficulty falling or staying asleep due to environmental noise participated in the study. Objective sleep architecture data were collected via a wireless electroencephalogram (EEG) sleep monitor and subjective data were obtained through analysis of daily sleep diaries and responses to study-specific user experience surveys. Four primary outcomes specified a priori were analyzed for statistical significance: objectively measured sleep onset latency (SOL), wake after sleep onset (WASO), number of awakenings, and perceived SOL. Exploratory analysis through descriptive statistics was conducted for an additional 36 secondary outcomes.ResultsUse of the digital wellness device was associated with reduced SOL both objectively and subjectively. Perceived SOL was 32.5% reduced (p < 0.001, difference in means 7.5 min, 95% CI 22.3%–41.4% faster), and objectively measured SOL was 13.3% reduced (p = 0.030, difference in means 2.7 min, 95% CI = 1.4%–23.8% faster). No statistically significant differences were found for other primary outcomes. Among the subjective secondary outcomes, 100% of participants felt the device blocked environmental noise, 86% reported falling asleep more easily, 76% felt they stayed asleep longer, and 82% felt overall sleep quality was improved. No differences were observed among objectively measured secondary outcomes.ConclusionsParticipants fell asleep faster when using the wearable wellness device. Participants also perceived sleep quality improvements with the intervention, although no objective differences were measured. These findings show promise for using noise-masking digital wellness devices in noisy environments to improve sleep quality.